The effect of orientation on prehension movement time. - van Bergen, E; van Swieten, L; Williams, J; Mon-Williams, M (Springer-Verlag, 2007)
We explored the relationship between hand orientation and movement time. Three groups of participants (n = 8 per group) were asked to grasp an object rotated in one of the following planes: (1) coronal; (2) sagittal; (3) horizontal. In the coronal plane, the rotational requirements directly mapped onto the neuromuscular demands associated with a single joint-level degree of freedom movement. A simple lawful relationship was found between the extent of rotation (pronation or supination) and duration. Reach-to-grasp movements to objects rotated in the sagittal and horizontal plane produced different movement patterns. These patterns increased the muscle level degrees of freedom recruited (higher neuromuscular demands) and movement duration increased correspondingly though not in a simple manner. The results of the present study show unambiguously that object orientation influences the duration of reach-to-grasp movements.